Effect of fine particle content on shear characteristics of geogrid-reinforced gravelly soil - Jiaquan WANG; Hong LIN; Yi TANG; Ying TANG (Shuiwen dizhi gongcheng dizhi)
Over prolonged service periods, reinforced gravel soil subgrades are susceptible to deterioration in interfacial mechanical properties due to the intrusion of fine particles. However, few studies focus on the interface of fine-grained polluted soil. To study the effect of fine particle content on the shear performance of gravelly soil, a series of direct shear tests of reinforced gravelly soil with different fine particle contents were carried out. The impacts of four different fine particle contents (0%, 10%, 20%, 30%) and three normal stresses (40, 60, 80 kPa) on the shear characteristics of the geogrid-gravel soil interface were analyzed, and the empirical formula of interfacial shear expansion coefficient was established. Results indicate that the shear stress-displacement curves of the reinforced gravelly soil direct shear tests are all of the stress softening type. With the increase in the fine particle content, parameters of peak strength and shear strength show an initial increase followed by a decrease trend. The particle interlocking force of well graded gravel soil is strong, which manifests as a high apparent cohesion in macroscopical. The dilatancy curve shows relative shear contraction, relative dilatancy, and relative shear contraction stages, and the occurrence of the maximum value of relative shear dilatation lags behind. The maximum dilation angle is closely associated with the peak shear strength. Through the dilation coefficient model, it is found that the smaller the fine particle content and normal stress are, the stronger the interfacial dilation is. This study can provide theoretical guidance for strength design and degradation protection of highway engineering.